Modification of Cassava Starch With Combination of Steaming and Acid Hydrolysis and Use as Encapsulant in Nanoencapsulation of Cocoa Leaf Crude Extract (Theobroma cacao L) - Ratih Kumala Dewi; Supriyanto Supiyanto; Yudi Pranoto; Agnes Murdiati (Indonesian Food and Nutrition Progress, 2022)
The utilization of native cassava starch in the food industry is limited. It needs a modified process to increase its utilization. This study aimed to evaluate the effect of a combination of steaming and acid hydrolysis and determine the best temperature and hydrolysis time that is suitable to apply as an encapsulant in the nanoencapsulation process of cocoa leaf crude extract. Modification of cassava starch used 50 ℃, 60 ℃, and 70 ℃ temperatures for 30, 60, and 90 minutes with HCl pH 1. The result showed that modified cassava starch produced from a combination of steaming and acid hydrolysis at 70℃ for 30 minutes has the best specifications with 60.48% solubility, 12.38% hygroscopicity, pasting profile (PV=48; BV=3; FV=66; SV=21). Then, it is combined with Arabic gum and used in the nanoencapsulation process using spray drying. This study showed that encapsulation can protect phenolic compounds of cocoa leaf crude extract resulting brownish-red color surrounded by a black circle. Nanocapsule powder has 13.56% moisture content, 350.3 nm particle size, 16.93 zeta potential, and 84.30% encapsulation efficiency. The combination of steaming and acid hydrolysis at 70 ℃ for 30 minutes produces modified cassava starch which is suitable for use as an encapsulant in the nanoencapsulation process of crude extract of cocoa leaves.